The promoter effect of potassium in CuO/CeO2 systems supported on carbon nanotubes and graphene for the CO-PROX reaction. Issue 15 (17th May 2016) - Dongil, A. B.; Bachiller-Baeza, B.; Castillejos, E.; Escalona, N.; Guerrero-Ruiz, A.; Rodríguez-Ramos, I.
Abstract : Improved performance of catalysts promoted with K was obtained in the CO-PROX reaction. Abstract : The effect of K promotion on the CO preferential oxidation (CO-PROX) reaction has been studied over Cu–CeO2 based catalysts supported on carbon nanotubes (CNT) and reduced graphene oxide (G). The catalysts were prepared with 3 wt% Cu and 20 wt% CeO2 loadings and 1 wt% K when promoted. In the CNT series, K loading was varied between 0.5 and 2 wt%. The catalytic performance and the characterization by powder X-ray diffraction (XRD), TEM-STEM, H2 -temperature-programmed reduction (H2 -TPR) and X-ray photoelectron spectroscopy (XPS) have been presented. TEM analysis showed that the type of carbon support has an important effect on the dispersion of ceria, with the latter being higher for the CNT support. Addition of K to the catalysts improved the conversion of CO at lower temperatures. The characterization results reveal that the observed increases in the Cu + species proportion and in lattice oxygen are related to the better catalytic performance.